ANALYSIS OF THE EFFECT OF FINANCIAL LEVERAGE AND LIQUIDITY TOWARDS STOCK VALUE AND PROFITABILITY AS THE INTERVENING VARIABLE IN TRADING COMPANIES LISTED AT INDONESIA STOCK EXCHANGE 2010-2014 - Haunan Damar; Umar Farouk; Winarto Winarto (JOBS (Jurnal Of Business Studies), 2015)
This research aims to investigate the effect of financial performance variables of Debt to EquityRatio (DER) and Current Ratio (CR) to the Stock Price with Return On Equity (ROE) as theintervening variable. The study is conducted to wholesale and retail companies that are listed inIndonesia Stock Exchange within 2010-2014 periods.The samples are chosen by using Purposive Sampling Method, where 15 companies inWholesale and Retail trading sub-sector are selected. There are two independent variables inthis research, they are Debt to Equity Ratio (DER) and Current Ratio (CR), one dependentvariable which is Stock Price as well as one intervening variable, Return on Equity (ROE). Analysis methods used in this research are multiple linear regression, simple linear regression and through path analysis.The result shows that both Debt to Equity Ratio (DER) and Current Ratio (CR) havesimultaneous positive and significant influence towards Return on Equity (ROE). Additionally,Return on Equity (ROE) variable positively and significantly affects the Stock Price. It can alsobe concluded that Debt to Equity Ratio (DER) and Current Ratio (CR) have an effect towardsStock Price with Return on Equity (ROE) as its intervening variable. It was found that DER hasa coefficient of 0,318 to the Stock Price through ROE, whereas CR has indirect effect of 0,2415towards Stock Price with ROE as intervening variable.Keywords: Debt to Equity Ratio, Current Ratio, Return on Equity, Stock Price